Cervical dilatation and preparation prior to outpatient hysteroscopy: a systematic review and meta‐analysis. (6th December 2020) - De Silva, PM; Wilson, L; Carnegy, A; Smith, PP; Clark, TJ
Abstract : Background: There are uncertainties about the benefit of routine cervical preparation and/or cervical dilatation before outpatient hysteroscopy. Objective: To determine if cervical preparation and/or routine mechanical dilatation reduces pain during outpatient hysteroscopy. Search strategy: MEDLINE, EMBASE, CINAHL and CENTRAL were searched on 19 October 2020, using keywords 'hysteroscopy', 'cervical preparation', 'cervical ripening', 'cervical dilatation', 'outpatient', 'office' and/or 'ambulatory' and associated medical subject headings. Selection criteria: Randomised controlled trials investigating the benefit of cervical preparation and/or cervical dilatation on pain in women undergoing outpatient hysteroscopy were included. Data collection and analysis: Two independent reviewers selected eligible trials and extracted data on pain, feasibility, adverse events and satisfaction/acceptability for meta‐analysis. Main results: The literature search yielded 807 records, of which 24 were included for review and 19 provided data for meta‐analysis. No trials investigated the role of routine mechanical cervical dilatation. Cervical preparation significantly reduced pain during outpatient hysteroscopy; standard mean difference (SMD) ‒0.67, 95% confidence interval (CI) ‒1.05 to ‒0.29. Feasibility also improved as priming provided significantly easier hysteroscopic entry (SMD 0.89, 95% CI 0.32–1.46), greater cervical dilatation (SMD 0.81, 95% CI 0.08–1.53) and shorter procedural times (SMD ‒0.51, 95% CI ‒0.88 to ‒0.13). Cervical preparation, however, incurred significantly more adverse effects, mainly comprising genital tract bleeding, abdominal pain and gastrointestinal symptoms (odds ratio 2.94, 95% CI 1.58–5.47). There were limited data regarding satisfaction, acceptability and complications. Conclusions: Cervical preparation reduces pain and improves feasibility associated with outpatient hysteroscopy but increases the risk of adverse effects. Tweetable abstract: Cervical preparation before outpatient hysteroscopy reduces pain, enhances feasibility but increases adverse effects. Tweetable abstract: Cervical preparation before outpatient hysteroscopy reduces pain, enhances feasibility but increases adverse effects.